Metode Runge-Kutta Orde 4 Dalam Penyelesaian Persamaan Gelombang 1D Syarat Batas Dirichlet - Yenci Brika Enkekes; Lutfi Mardianto (Indonesian Journal of Applied Mathematics, 2022)
The problem studied in this study was the movement of deviations in the equation of 1D waves on the rope given the initial deviation value. In this study, the equation of 1D waves with dirichlet boundary problems will be solved analytically using variable and numerical separation using the runge-kutta method approach of order 4. This research begins with examining equation models, solving analytical solutions, applying schemes to the final results of simulations. The decrease in equation model fissile is done by reviewing the working force on a piece of rope, solving an analytical solution with a variable separation method, and numerical completion resulting in the best simulation result with parameter c= 0.5 with time steps ∆x= 0.01 and time interval of 0 ≤ t≤ 1 resulting in a numerical approach close to its analytical solution up to t= 1 s and the influence of parameter c on the movement of wave deviations resulted in that the influence of parameter c affects the magnitude of the deviation of the wave, so the greater the value of parameter c, the smaller deviation of the wave and the faster the speed of the direction. Thus, it can be concluded that the runge-kutta method of order 4 in this study can be said to be one of the numerical approaches of the problem of 1D wave equations with dirichlet boundaries.